ANALISIS RASIO CAMEL UNTUK MENGUKUR TINGKAT KESEHATAN BANK PADA PT. BPRS BUMI ARTHA SAMPANG TAHUN 2019-2021 - Suwono; Mutia Pamikatsih; Yuli Amelianti (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study aims to determine the soundness level of the bank at PT BPRS Bumi Artha Sampang in 2019-2021 and to determine the development of its soundness level. This assessment uses the CAMEL method which consists of 5 aspects, namely aspects of Capital, Asset Quality, Management, Earning and Liquidity. The capital aspect uses the CAR ratio, the asset quality aspect uses the KAP ratio, the management aspect uses the NPM ratio, the earning aspect uses the ROA and BOPO ratios, and the Liquidity aspect uses the FDR ratio. Assessment of the soundness level of a bank is needed by various interested parties, especially for the bank so that it can find out the development of its soundness level and can be used as material for consideration and evaluation to determine future plans. This research is a type of quantitative descriptive research. Data source used is secondary data derived from the annual financial report of PT. BPRS Bumi Artha Sampang for 2019-2021 which was obtained directly from the bank. Data collection techniques in this study used document analysis techniques, namely by analyzing financial statements using the CAMEL method to determine the soundness level of the bank. The results of this research are in 2019 and 2020 PT. BPRS Bumi Artha Sampang is in an unhealthy position with a total score of 58.20 and 61.14. Whereas in 2021 the total CAMEL score will increase to 66.60 so that it is quite healthy. The development of the bank's soundness level is always increasing, but the bank must continue to improve its performance so that the bank's soundness level will be even better in the future.